FODDER PLANTS AND LIVESTOCK MAINTENANCE: INDIGENOUS KNOWLEDGE ASSOCIATED WITH GARO TRIBES OF MEGHALAYA, INDIA - SANGMA, DINGSMIT B; MANOHARA, T.N. (IJRDO-Journal of Applied Science, 2017)
The Garo tribes are inhabitants of Garo hill districts of Meghalaya. Due to their natural association anddependence on forest for daily needs, they have old practice to utilize forest products for food, fodder,medicine etc. Although, agriculture is the prime source of livelihood for a majority of rural population inthe Garo Hills, dependence on livestock as an alternative source of income is significant. Livestockmanagement is unique and is locally called ‘bathan’. The farmers have comprehensive indigenousknowledge of taxonomy, nutritional value of fodder plants and were able to identify 43 species of foddertrees under 32 genera belonging to 22 families. The farmers have some knowledge on utilizing locallyavailable plants for treating common ailments of their livestock’s. Forestry is the major source of leaf fodderand bedding material for livestock in the hills. Therefore, stall feeding practices for livestock should beencouraged. Farmers should be educated on the benefits of Agroforestry to encourage private plantation offodder tree species. For conserving the forest fodder- resources in a holistic manner there is a need for theintegration of ecological, environmental, social and economic sustainability in forest bio-diversity resourcemanagement.